USE OF STELLA SOFTWARE FOR THE MODELLING OF CLIMATE CHANGE IMPACTS ON WATER BALANCE FOR THE RIO YAQUI BASIN, SONORA, MEXICO - Tapia, Elia M.; Minjarez, Ismael; Espinoza, Inocente; Minjarez, Carlos (European Scientific Journal, ESJ, 2014)
Climate change in Northwest Mexico and its hydrological impact, including on water balance, water scarcity and flooding events, is a matter of great concern for the region due to its semiarid conditions. Changes in temperature, precipitation, and sea level would affect agriculture, farming, and aquaculture. The quality of water storages for human consumption may also be adversely affected. We evaluated possible changes in precipitation and temperature for the Rio Yaqui Basin in Sonora, Mexico and assessed the impact of those changes on water runoff, evapotranspiration and aquifer recharge for the years 2010 to 2099. For this purpose, we analyzed the results of a biascorrected and downscaled climate projection from the World Climate Research Programme's Coupled Model Intercomparison Project Phase 3 (WCRP-CMIP3) multi-model dataset: UKMO-HadCM3 from the Hadley Centre for Climate Prediction. The System Thinking Software STELLA 9.0.2 was used to dynamically visualize the effects of climate change on the Rio Yaqui Basin. In this software, the main components of water balance are simulated over the designated period of time with tools that include stocks and flow diagrams, causal loops, model equations and built-in functions. Climate change projections for the Rio Yaqui Basin showed highly variable runoff behaviors, indicating the possibility of frequent droughts, alternating with years of substantial runoff.